Ceropegia cryptobarbata sect. Chamaesiphon (Apocynaceae—Asclepiadoideae), a novel tuberous species from the Drakensberg foothills in South Africa - Heiduk, Annemarie (Phytotaxa, 2023)
A new species of Ceropegia (Apocynaceae—Asclepiadoideae—Ceropegieae) within sect. Chamaesiphon is described from the Drakensberg foothills in KwaZulu-Natal, South Africa. This new tuberous species, C. cryptobarbata, has deeply tubular-campanulate flowers with proportionally very short corolla lobes. The flowers are presented at ground-level and, despite having the gynostegium recessed into a long tube, they do not function as a pollinator trap as typical for Ceropegia s.str. The closest relative of C. cryptobarbata appears to be C. oiantha (formerly Brachystelma oianthum) with very similar vegetative and floral traits. Ceropegia oiantha was thus far considered outstanding in the section based on its deeply tubular-urceolate, egg-shaped flowers which are also presented lying on the ground. With the discovery of C. cryptobarbata, the sect. Chamaesiphon has gained a second member with such unusual flowers. Ceropegia cryptobarbata is clearly distinct from C. oiantha in particular by its densely barbate gynostegium which is furthermore exceptional in sect. Chamaesiphon.